Oxygen consumption of carps during live transportation - Aravindakshan, P K; Singh, S K; Sarkar, Bikash; Majhi, D; Jena, J K; Pani, K C; Muduli, H K; Ayyappan, S; Mohapatra, B C; Sarangi, N (Indian Journal of Fisheries, 2012)
A study was undertaken to determine the oxygen consumption rate of live Asiatic carps during transportation in fibre reinforced plastic (FRP) tank of 1280 l capacity fitted inside a jeep trailer. Six experiments were conducted using table size fishes (425-1060 g) of Indian major carps viz., Catla catla, Labeo rohita, Cirrhinus mrigala and the exotic carps Hypophthalmichthys molitrix, Cyprinus carpio and Puntius gonionotus. Dissolved oxygen content and other water quality parameters were estimated at regular intervals during live fish transportation. The mean oxygen consumption values were found to be in the range of 15.7 - 58.2 mg fish-1 h-1 and the computed oxygen consumption rates were 19.74 - 70.58 mg kg fish-1 h-1 during transportation. Among the surface dwelling fishes, computed oxygen consumption rate was lower for silver carp (54.8 mg kg fish-1 h-1) as compared to catla (70.58 mg kg fish-1 h-1). Among the column living fishes, the oxygen consumption was lower for silver barb (50 mg kg fish-1 h-1) compared to rohu (68.9 mg kg fish-1 h-1). Common carp showed lowest value (19.74 mg kg fish-1 h-1) compared to mrigal (35.8 mg kg fish-1 h-1) among the bottom living fishes. The actual average oxygen consumption has shown clear-cut downward trends from the surface via column to bottom dwelling fishes.